GAMBARAN EFEK SAMPING ANTIPSIKOTIK PADA PASIEN SKIZOFRENIA RAWAT INAP DI RS. GRHASIA YOGYAKARTA - jualeha, julaeha; ananda, vitarani; pradana, dimas (Farmasains : Jurnal Ilmiah Ilmu Kefarmasian, 2016)
This study aimed to profile the use of antipsychotics, the prevalence of DRPs events, and to compare the prevalence of DRPs use of antipsychotics in patients with schizophrenia in Grhasia hospital. This study is an observational study with cross sectional descriptive. Patients who were included in this study were patients with schizophrenia in the period 2007-2009 Grhasia Hospital who met the inclusion criteria, number of patients who were taken in this research are as many as 300 patients with a stratified sampling method. Data collection was performed retrospectively through medical records included patient characteristics, drug use data, and side effect event. From the data were collected regarding the percentage of use of antipsychotics. The results showed that administration of combination klorpromazin and haloperidol, an antipsychotic of the most widely used for the treatment of schizophrenia with a percentage over the period 2007, 2008, and 2009 are 60%, 70%, and 47%. Percentage side effect event over the period 2007, 2008, and 2009 are 31%, 28 % dan 14 %.